Risk Identification and Prevention of Supply Chain Operation in Small and Medium-Sized Livestock Farms - Man Xu; Xinglong Yang; Zhiru Sun (Systems)
In recent years, there has been rapid development in Chinese small and medium-sized livestock farms, accompanied by an increase in operational risks within the supply chain. To ensure the stability and sustainability of supply chain operations in small and medium-sized livestock farms, it is essential to thoroughly analyze their potential hazards and formulate effective prevention strategies. This paper employs the relevant supply chain theories, combined with previous research and expert interviews, to conduct an empirical analysis of supply chain operation risks in small and medium-sized livestock farms, with a specific focus on pig farms, beef cattle farms, laying hen farms, and broiler farms. The research indicates that the supply chain operation risks faced by small and medium-sized livestock farms primarily stem from external environmental factors and production-related challenges. Furthermore, external environmental risks predominantly arise from market fluctuations and compliance with environmental regulations, while production risk mainly pertains to disease safety. Based on the research findings, this paper proposes specific measures for risk prevention, including the strengthening of external environmental security, driving production innovation capacity, strengthening market forecasting capacity, constantly enhancing environmental awareness, and strengthening epidemic prevention efforts.